1974
DOI: 10.1073/pnas.71.2.544
|View full text |Cite
|
Sign up to set email alerts
|

Site of J Chain Attachment to Human Polymeric IgA

Abstract: A fragment containing J chain was released from human polymeric myeloma IgA protein by cyanogen bromide cleavage. The identity of the fragment was determined by its electrophoretic mobility and antigenic determinants. After purification by gel filtrations and DEAE-Sephadex chromatography, this fraction appeared similar (with respect to its amino acid and carbohydrate compositions and its peptide maps) to the J chain isolated from this IgA protein; the molecular weight was 17,000 i 100. Upon reduction and alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The ability of IgA and IgM to form polymers has been associated with the presence of the 18-amino-acid C terminal tailpieces on α and μ chains, which include the penultimate Cys residue to which J chain is attached (Mestecky et al, 1974b;Mestecky and Schrohenloher, 1974). Indeed, the addition of this tailpiece to IgG results in the formation of pIgG with interesting functional consequences (Sørensen et al, 1996;Smith et al, 1995).…”
Section: α-Chainsmentioning
confidence: 94%
See 3 more Smart Citations
“…The ability of IgA and IgM to form polymers has been associated with the presence of the 18-amino-acid C terminal tailpieces on α and μ chains, which include the penultimate Cys residue to which J chain is attached (Mestecky et al, 1974b;Mestecky and Schrohenloher, 1974). Indeed, the addition of this tailpiece to IgG results in the formation of pIgG with interesting functional consequences (Sørensen et al, 1996;Smith et al, 1995).…”
Section: α-Chainsmentioning
confidence: 94%
“…Subsequent studies revealed that this chain was glycosylated, with a molecular mass of 15-16 kDa, and was linked by disulfide bridges to the Fc fragment of polymeric IgM or IgA of secretory and serum (myeloma) origin (Mestecky and Schrohenloher, 1974;Mestecky et al, 1974b;Garcia-Pardo et al, 1981). On the basis of the given criteria (molecular mass, fast electrophoretic mobility, characteristic amino acid composition, and immunochemical cross-reactivity), the presence of J chain has been established, with varying degrees of confidence, in pIg from many vertebrate species including mammals (human, monkey, rabbit, mouse, pig, dog, goat, cat, cow, horse, rat, guinea pig, and sheep), birds (chicken and pheasant), reptiles, (two species of turtles, Trachemis scripta, and Pelodiscus sinensis), amphibians (frog and toad), and fishes (catfish and nurse sharks) (Kobayashi et al, 1973;Inman and Mestecky, 1974;Iwata et al, 2002;Koshland, 1985;Mikoryak et al, 1988;Kulseth and Rogne, 1994;Takahashi et al, 2000;Hohman et al, 1997Hohman et al, , 2003Xu et al, 2009).…”
Section: J Chainmentioning
confidence: 95%
See 2 more Smart Citations
“…J chain was isolated from an IgA2~, polymemc myeloma protein (8) and coupled to BSA as described by Brandtzaeg (5). Rabbits were immunized three times, at 1-mo intervals, with the antigen m complete Freund's adjuvant.…”
Section: Methodsmentioning
confidence: 99%